Synthesis of SnO2/TiO2 micro belt fibers from polymer composite precursors and their applications in Li‐ion batteries. Issue 2 (13th September 2021) - Gonzalez, Gabriel; Hasan, Md Toukir; Ramirez, Daniel; Parsons, Jason; Alcoutlabi, Mataz
Abstract: SnO2 /TiO2 micro belt–fiber composites were successfully synthesized using centrifugal spinning and subsequent heat treatment of SnO2 /TiO2 /polyvinylpyrrolidone (PVP) precursor fibers. SnO2 /TiO2 /PVP precursor solutions consisting of different ratios of SnO2 to TiO2 were prepared by mixing Tin (II) 2‐ethylhexanoate and titanium (IV) butoxide with PVP in ethanol. The SnO2 /TiO2 /PVP mixture was heat treated in air at 700°C, which resulted in the formation of SnO2 /TiO2 micron‐sized fibers with a belt‐shaped morphology. Structural, morphology, and surface chemistry characterization of the materials was performed using powder X‐ray diffraction, scanning electron microscopy (SEM)/energy‐dispersive X‐ray spectrometer, and X‐ray photoelectron spectroscopy analyses. SEM analysis showed the SnO2 /TiO2 composite fibers with (3:2) ratio had a micro belt morphology with particles on the surface. The material was tested as an anode material for lithium‐ion batteries (LIBs); the composite fiber electrode delivered an initial capacity of 1200 mAh g −1 at 100 mA g −1 . The capacity was observed to decrease to 279 mAh g −1 after 70 cycles; however, the sample retained a columbic efficiency of 99%, which indicated good reversibility. Due to the high surface area and unique structure, the as‐synthesized SnO2 /TiO2 composite fibers may be promising for sensor and LIB applications.